Aktivasi MPCK Guru Matematika dalam Pembelajaran Geometri: Studi Komparatif pada Guru yang Telah dan Belum Mengikuti PPG - Mutammam, Muhamad Badrul; Wulandari, Evi Novita; Firmansyah, Frenza Fairuz; Afifah, Ngizatul; Kunaza Fazira, Shima; Angrenani, Arin Berliana (Media Pendidikan Matematika, 2026)
This study aims to describe and compare the activation of mathematics teachers’ Mathematics Pedagogical Content Knowledge (MPCK) in geometry instruction in two observed cases: one teacher who had participated in the Professional Teacher Education Program (PPG) and one teacher who had not participated in PPG. This study used a comparative qualitative case study design involving two junior high school mathematics teachers with more than ten years of teaching experience. Both teachers taught the same topic, namely cubes in flat-sided solid geometry, in two different Grade 8 classes with 36 students in each class. Data were collected through video-based classroom observations, analysis of lesson plans and students’ worksheets, and semi-structured interviews. The video data were transcribed, segmented into instructional episodes, coded using MPCK indicators, and triangulated with document and interview data. The findings show that the teacher who had participated in PPG displayed more varied MPCK activation, particularly in the use of concrete and visual representations, mathematical communication, classroom discussion, formative responses, and responses to students’ misconceptions about edges, faces, cube nets, and surface area. In the observed cases, participation in PPG may be associated with more varied MPCK activation; however, this relationship cannot be interpreted causally because the study involved only two teachers in a limited context. The findings also indicate that Mathematical Content Knowledge (MCK) functions as an important foundation for MPCK, but MPCK becomes visible when content knowledge is transformed into representations, guiding questions, discussion, and formative feedback that support students’ conceptual understanding